GROWTH AND PRODUCTION OF TEA PLANT (Camellia sinensis (L.) O Kuntze) AFTER PRUNING WITH BIO-ORGANOMINERAL AMELIORANT - Restu Wulansari; Faris Nur Fauzi Athallah; Eko Pranoto; Maryono Maryono; Didit Adi Darmawan; Budhy Agung Supriyanto (Puslitbang tekMIRA, 2021)
Tea plant (Camellia sinensis (L.) O Kuntze) is one of the important plantation commodities that has long been cultivated in Indonesia. Mineral based ameliorant fertilization is one of the important factors to produce high productivity and maintenance of healthy plants. Ameliorant bio-organomineral (BIOM) is a fertilizer that utilizes mineral resources, potential microbes, and organic matter. This study aimed to determine the effect of BIOM's ameliorant on plant health and tea productivity after pruning. The Randomized Block Design (RBD) was accomplished by 8 treatments and three replications (100% conventional fertilizer, 100% BIOM, 80% single fertilizer + 100% BIOM, 80% conventional fertilizer + 80% BIOM, 80% conventional fertilizer + 60% BIOM, 60% conventional fertilizer + 100% BIOM, 60% conventional fertilizer + 80% BIOM, and 60% conventional fertilizer + 60% BIOM). The results showed that there was a significant effect of the combination of conventional fertilizer and BIOM ameliorant on shoot production and pekoe percentage, but not significantly different in tipping production, pekoe shoot ratio and banji shoots. The combination of 60% conventional fertilizer and 60% BIOM showed the highest total production of 31.81 kg/plot. Shoot production in the BIOM treatment was 17.36% higher than that of the conventional fertilizer application. The application of BIOM ameliorant was able to improve the plant health after pruning on the GMB 7 clone.